EVALUASI MUTU FISIKOKIMIA DAN ORGANOLEPTIK MODIFIKASI KUE SATU BERBASIS TEPUNG PISANG (Quality Evaluation of Physicochemical and Organoleptic Characteristic of Modified Satu Cake Based on Banana Flour) - Sarifudin, Achmat; Ekafitri, Riyanti; I.M, Nur Kartika (Baristand Industri Banda Aceh, 2015)
Satu cake is a traditional cake usually made from mixture of mung bean flour and sugarflour. The research had proposed Satu cake by subtituting mung bean flour to banana flour. The objectiveof this research was to evaluate the quality of Satu cake as the influence of the differences ratio ofbanana flour and sugar flour 1:1, 1:2, and 1:3, respectively and 3 replications for each The physicalquality properties (whiteness and hardness), chemical properties (water, ash, protein, fat, carbohydrate,and fiber content) as well the sensory evaluation were evaluated. Results showed that increasing thepercentage of banana flour in the Satu cake formula tended to increase the hardness value, water content,ash content, protein content, meanwhile the whiteness index tended to decrease. The different ratiobetween sugar flour and banana flour was not significantly effect to the fat content, carbohydratecontent, fiber content of the Satu cake sample. The whiteness degree of the Satu cake ranging from 39,25-44,23%, hardness value from 0,46 to 0,53 mm/gr/sec, water content from 17,2 to 20,1%, ash content from0,8 to 1,3%, protein content from 4,4 to 6,6%, fat content from 0,3 to 0,4%, carbohydrate content from 71to 74,4%, fiber content from 2,8 to 3,2%. Result of sensory evaluation recommended the most favoredamong the Satu cake samples was sample from formulation sugar flour : banana flour 1:1.